A SURVEY PAPER ON EXTRACTION OF OPINION WORD AND OPINION TARGET FROM ONLINE REVIEWS - Pranita Ramesh Sasane; Pawan Kumar (International Journal of Innovations in Engineering Research and Technology, 2021)
Opinion mining is nothing but mining opinion targets and opinion words from online reviews. To find opinion relation among them partially supervised word alignment model have used. To find confidence of each candidate graph based co-ranking algorithm have used. Further candidates having confidence higher than threshold value are extracted as opinion word or opinion targets. Compared to previous approach syntax-based method this method can give correct results by eliminating parsing errors and can work on reviews in informal language. Compared to nearest neighbor method this method can give more precise results and can find relations within a long span. Also to decrease error propagation graph based co-ranking algorithm is used to collectively extract opinion targets and opinion words. Also to decrease probability of error generation penetration of high degree vertices is done and decrease effect of random walk.